Marco conceptual para el análisis del impacto socio espacial de la peatonalización de la carrera séptima (2014)
This article is presented as advance research “partner pedestrian space race between 26th Street and Seventh Avenue 19 Impact”. Looking to continue the previous article in which the historical components that have accompanied the process of spatial construction career seventh in the study reach were exposed. This second phase aims to observe from a conceptual framework for new alternatives analysis, design and understanding of the city and its public spaces. This approach seeks to create a conceptual support from several variables to analyze and propose solutions to the impact it has had the pedestrianization of the seventh race.